Kedu Chickens Exhibit Better Resilience to Thermal Stress During the Two Weeks Prior to Market Age Compared to Broiler Chickens - Tiya, N. A. D.; Suprijatna, E.; Mangisah, I.; Agusetyaningsih, I.; Pandupuspitasari, N. S.; Sugiharto, S. (Tropical Animal Science Journal, 2026)
Information about resilience to thermal stress is important for establishing the optimum rearing temperature for chickens. This study investigated the effects of heat stress on the physiological and hematological responses of Kedu and broiler chickens. Based on a 2×2 factorial arrangement, 192 male Kedu and broiler chickens were raised at temperatures of 23.83 ± 0.23°C or 35.33 ± 1.78°C. Sampling and data measurement were conducted after two weeks of rearing. Heat stress had no effect on the weight gain of the Kedu chickens, whereas the broiler weight gain fell (p≤0.05). Heat stress reduced feed consumption, while increasing water intake, feed conversion ratio (FCR), rectal temperature, heart rate, and respiratory rate (p≤0.05). The heterophil-to-lymphocyte ratio of the Kedu chickens was higher than that of broilers (p≤0.05), while heat stress increased glucose and uric acid levels in the broilers (p≤0.05), but not in the Kedu chickens. Heat stress also increased heterophils. In addition, mean corpuscular volume and mean corpuscular hemoglobin levels were higher in the Kedu chickens than in the broilers, while platelet counts were higher in the broilers (p≤0.05). Erythrocyte, hemoglobin, and hematocrit levels decreased during heat stress (p≤0.05), while platelet distribution width (PDW) in the broilers increased (p≤0.05). Blood proportion to live chicken body weight was higher in the Kedu chickens than in the broilers, while heat stress reduced the blood and feather proportions in the broilers (p≤0.05). Heat stress also reduced the liver weight of the Kedu chickens, as well as that of the thymus and Bursa of Fabricius in both types of chicken (p≤0.05). The Kedu chickens had higher gizzard, spleen, and Bursa of Fabricius weights than the broilers (p≤0.05). In conclusion, compared to the broilers, the Kedu chickens demonstrated greater tolerance to heat stress, as indicated by their unaffected weight gain, blood glucose levels, PDW, and feather proportion.